ISLAMIC EDUCATION AS A MEANS OF EVELOPING HUMAN NATURE - Saleh, Riskawati; Bustam, Betty Mauli Rosa (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Fitrah as the initial character or human nature that is carried from the beginning when humans are born, has two sides namely good or bad, in its distribution, thus allowing the emergence of deviations. The aim of this study is to analyze how Islamic education is a means of developing human nature. This research is qualitative and takes the form of library research, which is conducted by tracing various sources of literature or literature in the form of books, as well as indexed publication articles related to Islamic education and human nature. The results of the analysis found that there are several khashiyat, or special features, in human nature as potential given by Allah SWT, including physical needs and gharizah (instincts), which consist of the instinct to continue offspring, the instinct for self-defense, and the instinct for religion. The control process in channeling instincts (nudges) in human nature requires the intervention of Islamic education in its direction so that deviations do not occur and are able to form students into human beings who have Islamic syakhsiyah (personality). Islamic educational institutions that play a role in the process of Islamic education include family, school, and community institutions.